The Influence of Leadership and Motivation on The Performance of Employees of The Subbagpers Bagrenmin Korsabhara Indonesian National Police Security Agency - Mistin Helminingsih; Harries Madiistriyatno; Nurwulan Kusumadewi (Dinasti Publisher, 2026)
This study has the following research objectives: To determine the influence of leadership on employee performance, To determine the influence of work motivation on employee performance, and To determine the influence of leadership and work motivation together on employee performance of Subbagrenmin Korsabhara Baharkam Polri. The t-test results show a calculated t value of 4.605, which is greater than the t-table of 2.004, so the hypothesis states that leadership influences employee performance is accepted. The t-test results on the work motivation variable show a calculated t value of 8.143, which is greater than the t-table of 2.004, so the hypothesis states that there is an influence of work motivation on employee performance is accepted. The Adjusted R Square value of 0.781 indicates that 78.1% of employee performance variations can be explained by leadership and work motivation variables simultaneously. While the remaining 21.9% is influenced by other factors outside this study.